Another productive year for our Journal - Iacopo Borsi (Acque Sotterranee)
In this year (2024), as in the past, our Journal has provided an important contribution to hydrogeology. We can confirm that we have maintained a high level of editorial quality, with a good balance among the three pillars behind the journal: a bridge between applications and research, the promotion of Italian hydrogeology, and the connection between it and the international context, with particular focus on the Euro-Mediterranean region....